1998
DOI: 10.1890/0012-9658(1998)079[1562:efcsop]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal Fungal Community Structure of Pinyon Pines Growing in Two Environmental Extremes

Abstract: We used molecular techniques to examine the ectomycorrhizal fungal community associated with pinyon pine (Pinus edulis) growing in two soil types in a semiarid region of northern Arizona: cinder soils low in nutrients and moisture, and sandy‐loam soils with higher moisture and nutrient levels. Pinyon performance (e.g., growth, reproduction, water stress) has been shown to be markedly lower in cinder than in sandy‐loam environments. Fungal community composition and richness were determined using RFLP (restricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(143 citation statements)
references
References 37 publications
8
132
3
Order By: Relevance
“…Only a few of the ECM morphotypes found were abundant and well distributed; most were rare species which occurred sporadically, a common pattern reported at any taxonomic level (Baar et al 1999;Dahlberg et al 2001;Durall et al 1999;Gardes and Bruns 1996;Gehring et al 1998;Grogan et al 2000;Hagerman et al 1999;Peter et al 2001;Stendell et al 1999;Taylor 2002). Most studies on ECM community structures suggest that C. geophilum and ECM in the Russulaceae, Thelephoraceae and other resupinate fungi dominate within all ECM communities (Dahlberg 2001;Horton and Bruns 2001;Peter et al 2001).…”
Section: Discussionmentioning
confidence: 92%
“…Only a few of the ECM morphotypes found were abundant and well distributed; most were rare species which occurred sporadically, a common pattern reported at any taxonomic level (Baar et al 1999;Dahlberg et al 2001;Durall et al 1999;Gardes and Bruns 1996;Gehring et al 1998;Grogan et al 2000;Hagerman et al 1999;Peter et al 2001;Stendell et al 1999;Taylor 2002). Most studies on ECM community structures suggest that C. geophilum and ECM in the Russulaceae, Thelephoraceae and other resupinate fungi dominate within all ECM communities (Dahlberg 2001;Horton and Bruns 2001;Peter et al 2001).…”
Section: Discussionmentioning
confidence: 92%
“…Field studies of ECM associated with black spruce (Robertson et al 2006 ) and subalpine fir (Kranabetter et al 2009 ) also found variations in ECM community structure due to differences in moisture. A study of ECM communities from pinyon pine trees growing in different soils noted that soil type was linked to fungal community composition (Gehring et al 1998 ). A recent study (Karst et al 2011 ) found that Douglasfir seedlings from lowmoisture soils had higher levels of ectomycorrhizal colonization than those from medium and high moisture soils.…”
Section: Discussionmentioning
confidence: 99%
“…As with other areas of mycology, molecular studies have recently revolutionized the study of ECM fungal diversity. In addition to clarifying the discrepancy between above and belowground fungal diversity, molecular surveys also revealed ECM communities as hyperdiverse (particularly when compared to plant host diversity) and composed mostly of rare species (Gehring et al, 1998, Taylor, 2002, Avis et al, 2003, Horton & Bruns, 2005, Walker et al, 2005, Avis et al, 2008, Morris et al, 2008, Branco & Ree, 2010. Figure 5 shows the typical patterns underlying ECM fungal communities: unsaturated species accumulation curves reveal the difficulty in obtaining complete community descriptions and a rank-frequency diagrams illustrate the rarity of most species.…”
Section: Ectomycorrhizal (Ecm) Fungal Diversitymentioning
confidence: 99%